Humanization, Liberation, and Transcendence in the Works of Achmad Charris Zubair - Zahwa Aliya Rastiani; Alvira Auzia Aflaha; Ilham Rabbani; Rizal Hidayat Ramadan; Yoisa Zoey El Sherin; Endah Nur Halimah; Risma Dwi Julianti; Itsna Nabilah (Journal of Social Science and Humanities, 2026)
This studi aims to examine the prophetic aspects in two poems by Achmad Charris Zubair entitled “Elegi Buat Mbayuku yang Pergi” and “Perjalanan ke Arah Bukit”. Prophetic literature, as developed by Kuntowijoyo, is an approach in literary studies that emphasizes three main aspects humanization, liberation, and transcendence. Through the descriptive qualitative method, this study seeks to interpret the deep meaning contained in the poems in a spiritual and deep thinking manner. The results of the study show that Achmad Charris Zubair’s peoms provide strong peotic reflections on inner struggles in the face of suffering, loss, and the search for the meaning of life. The values of humanization are reflected in empathy for others and recognition of human dignity. Liberation is shown in the form of resistance to social injustice and efforts to liberate the mind from wordly attachments. Meanwhile, teh value of transcendence is discussed in the comtemplation of the existence of God, the universe, and the soul’s journey towards kinner peace. These there aspects form a structure of meaning that is not only aesthetic, but also ethical and philosophical.